SYSTEM THINKING APPROACH TO IMPROVE NEW AND RENEWABLE ENERGY MANAGEMENT IN INDONESIA ELECTRICITY SECTOR - Prabandono Mahardi, Johan; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2017)
Abstract: Indonesia?s new and renewable energy (NRE) electricity sector has a long history with changing regulations and actors while continuously struggling with issues in coordinating stakeholder?s objectives, complex regulation and licensing, electricity tariffs, lack of expertise, and financing. Due to number of involved actors and regulations, it requires systemic approach to observe the impact of one variable to overall objective of the sector. Study is conducted using combination of system thinking methodologies. Compiled from literature studies, non-participant observation, and interviews with respondents representing the main actors, a causal loop diagram was developed. Behavioral patterns or archetypes were identified to produce recommendations in improving the system condition. Finally, a preliminary dynamic modelling was developed using stock and flow diagram showing the variables and their interaction more quantitatively. It provides an initial outlook on the parameters within the system to be considered in the decision making process and policy development.Keywords: System Thinking, New and Renewable Energy, Electricity, Causal Loop Diagram, Archetype